Epigenetic repression of gene expression controls the initial phases of gametocytogenesis in the malaria parasite, Plasmodium falciparum - Birkholtz, Lyn-Marie (University of Pretoria, 2021)
Thesis (PhD (Biochemistry))--University of Pretoria, 2021.